2006
DOI: 10.2174/157339606778699662
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Newborns with Neonatal Seizures: Risk Factors and Predictors

Abstract: Neonatal seizures (NS) are generally an acute manifestation of disturbance of the developing brain and are very common in the first weeks of life. Many studies have been published concerning risk factors, etiology, identification, treatment and outcome of newborns with seizures, however, an important question as why the outcome is so diverse among neonates with seizures is still open to discussion. A literature review was performed with the help of the Medline database by crossing the key words neonatal seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
(69 reference statements)
0
0
1
Order By: Relevance
“…Seizures are the most important clinical manifestation of neurological disorders in the neonatal period. Even though seizures are usually reported to occur more frequently in premature infants,11 in the present study, we observed a predominance of seizures in term newborns with birth weight appropriate to gestational age. These results agree with another studies done by Gacias da Silva et al12 and Holand M et al13 This finding might be related to regional peculiarities of maternal and birth care or perhaps due to the high incidence of perinatal asphyxia in our cohort, which is a more common cause of seizure in term newborns rather than preterms in whom interventricular hemorrhage and infections are the most frequent causes 14…”
Section: Discussioncontrasting
confidence: 65%
“…Seizures are the most important clinical manifestation of neurological disorders in the neonatal period. Even though seizures are usually reported to occur more frequently in premature infants,11 in the present study, we observed a predominance of seizures in term newborns with birth weight appropriate to gestational age. These results agree with another studies done by Gacias da Silva et al12 and Holand M et al13 This finding might be related to regional peculiarities of maternal and birth care or perhaps due to the high incidence of perinatal asphyxia in our cohort, which is a more common cause of seizure in term newborns rather than preterms in whom interventricular hemorrhage and infections are the most frequent causes 14…”
Section: Discussioncontrasting
confidence: 65%